1992
DOI: 10.1161/01.cir.85.4.1572
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between left ventricular untwisting and filling. Accentuation by catecholamines.

Abstract: BACKGROUND Efficient early diastolic filling is essential for normal cardiac function. Diastolic suction, as evidenced by a decreasing left ventricular pressure during early filling, could result from restoring forces (the release of potential energy stored during systolic deformation) dependent on myofilament relaxation. Although these restoring forces have been envisioned within individual myofibers, recent studies suggest that gross fiber rearrangement involving the connective tissue network occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
243
0
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(264 citation statements)
references
References 29 publications
19
243
0
2
Order By: Relevance
“…The method used in this study was optimized for assessment of systolic function and early diastole. These advantages of the DTI method may facilitate assessment of LV torsional dynamics, including the relationship between systolic torsion and diastolic suction 7,16,32 (based on the cylinder model of Ingels et al 6 or the Torrent-Guasp model: creation of a suction force by contraction of a ventricular myocardial band 36 ) and may give insight into tissue 7,18,19 and molecular [21][22][23] aspects of ventricular mechanics. Diastole is a very complex process that cannot be separated from the preceding systole.…”
Section: Advantage Of the Current Dti Methods For LV Torsion Assessmentmentioning
confidence: 99%
“…The method used in this study was optimized for assessment of systolic function and early diastole. These advantages of the DTI method may facilitate assessment of LV torsional dynamics, including the relationship between systolic torsion and diastolic suction 7,16,32 (based on the cylinder model of Ingels et al 6 or the Torrent-Guasp model: creation of a suction force by contraction of a ventricular myocardial band 36 ) and may give insight into tissue 7,18,19 and molecular [21][22][23] aspects of ventricular mechanics. Diastole is a very complex process that cannot be separated from the preceding systole.…”
Section: Advantage Of the Current Dti Methods For LV Torsion Assessmentmentioning
confidence: 99%
“…Subsequent elastic recoil of twist deformation during isovolumic relaxation releases restoring forces, contributing to LV relaxation and early diastolic filling 149 , 150 . LV torsion is a function of LV contractility and varies linearly with EF 151 , while diastolic untwisting contributes to LV filling through suction generation 152 , 153 . Pertinent to the study of diastolic function is the dynamics of LV untwisting that commences in late systole but mostly occurs during the isovolumetric relaxation and is largely completed at the time of mitral valve opening 152 .…”
Section: Torsion/twist Mechanicsmentioning
confidence: 99%
“…LV torsion is a function of LV contractility and varies linearly with EF 151 , while diastolic untwisting contributes to LV filling through suction generation 152 , 153 . Pertinent to the study of diastolic function is the dynamics of LV untwisting that commences in late systole but mostly occurs during the isovolumetric relaxation and is largely completed at the time of mitral valve opening 152 . The rate of untwisting correlates with τ, is independent of left atrial pressure 154 and was observed to remain constant during volume loading.…”
Section: Torsion/twist Mechanicsmentioning
confidence: 99%
“…Axes are radial (R) using the direction perpendicular to wall; fiber (F), tangent to surface and parallel to local fiber direction at either epicardium or endocardium; and cross-fiber (X), tangent to surface and perpendicular to F. M 1270 3 40 56 ASA, ACEI 7 49/M 8300 3 60 3 40 36 ASA, BB, ACEI 8 59/F 4847 0 100 3* 40 46 ACEI, ASA 9 55/F 952 3 50 58 ASA, ACEI 10 70/M 7260 3 80 3 40 43 ASA, BB 11 74/M 3165 2 95 2 30 47 ASA 12 59/M 2950 3 90 3 20 10 and to calculate the normal and shear strains of the myocardium. 11 A 3D deformation analysis of the myocardium can be performed with the use of perpendicular short-and long-axis images. 12 The LV myocardium was thus divided into 32 small cuboids encompassing the entire LV except for the apex (Figure 1).…”
Section: Measurement Of Regional Myocardial Viability With Petmentioning
confidence: 99%